Experimental study on seismic behavior of a novel plug-in self-lock joint for modular steel construction. (15th February 2019) - Dai, Xiao-Meng; Zong, Liang; Ding, Yang; Li, Zhong-Xian
Highlights: A plug-in self-lock joint for modular steel construction is proposed. Working mechanism is introduced and uplift behavior is verified through pull-out test. Eight full-scale specimens are tested and seismic behavior is evaluated and discussed. A simplified mechanical model is developed and validated through test results. Abstract: The joints between modular units are always key issues for modular steel construction. Previous types of joints require extra operation spaces for connection and will have conflicts with internal finish and installed services. Therefore, these types of joints cannot be adopted for middle columns in modular steel construction. Regarding this condition, a novel type of joint, plug-in self-lock joint was proposed in this study. The working mechanism of the plug-in self-lock connection was introduced, and a pull-out test was conducted to investigate the tensile behavior of the connection. Then eight full-scale joint specimens using the novel connection were tested under quasi-static load to investigate the seismic behavior of the plug-in self-lock joints. The test results offered failure mode, strength, stiffness, ductility and energy dissipation of the plug-in self-lock joints. Based on the experimental observation, a simplified mechanical model was developed to predict the behavior of this novel joint in elastic stage, and was validated through test results. Recommendations for the design of the joints were given accordingly.